Peningkatan Kapasitas Kader Edukasi Stunting dengan Metode Emo-Demo bagi Keluarga - Ariyanti, Rea; Susanti, Rahmi; Masithah; G, Ike Anggraeni; AB, Ismail (Penerbit Goodwood, 2025)
Purpose: This activity aims to increase cadres’ capacity to provide education related to stunting prevention through Emo-Demo. Research methodology: This activity takes the form of socialization and Emo-Demo training as a new method for providing education regarding stunting to at-risk families, which is carried out in five stages: preparation, socialization, Emo-Demo training, mentoring, and evaluation. The target of this activity was an acdre of 24 people. Results: All stages were carried out according to the established plan. Evaluation of the implementation of Emo-Demo revealed that there was an increase in the average understanding of cadres regarding education using Emo-Demo, from 60 to 80. Conclusions: Capacity building for cadres in providing stunting prevention education to at-risk families through the Emo-Demo method was successfully implemented. Based on the evaluation of Emo-Demo implementation, there was an increase in cadres’ average understanding of education using the Emo-Demo method, from 60 to 80. Additionally, the evaluation results showed a significant improvement in the average understanding of at-risk families regarding the education delivered by cadres, increasing from 44 to 100. Limitations: Prioritizing certain themes such as health problems in the field of nutrition such as stunting. Contribution: Increasing the capacity of cadres in providing stunting prevention education to at-risk families through Emo-Demo has been implemented well. The results of the evaluation of the understanding of at-risk families regarding the education provided by cadres using Emo-Demo also experienced an average increase from 44 to 100.